Perancangan Bahan Ajar Berbasis Multimedia untuk Membangun Pengalaman Belajar yang Menarik dan Interaktif - Dwi Margaretta Manihuruk; Tata Sutabri (Journal of Creative Student Research, 2024)
This research aims to design multimedia-based teaching materials that can improve students' learning experiences to be more interesting and interactive. The research method used is research and development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The research results show that multimedia-based teaching materials are effective in increasing students' motivation, understanding of concepts, and participation in the learning process. The teaching materials are designed using multimedia elements such as videos, animations, interactive simulations and gamification-based quizzes. Implementation and evaluation on students shows significant results in supporting interesting and effective learning.